2023
DOI: 10.1210/endocr/bqad045
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced Sertoli Cell Injury Through p38-MAPK and Related Signaling Proteins—A Study by RNA Sequencing

Abstract: Environmental toxicants, such as cadmium, found in foods, water and consumer products are known to induce male reproductive dysfunction. However, the underlying molecular mechanism(s) by which cadmium-induced Sertoli cell injury as manifested by a disruption of the blood-testis barrier remains unknown. Interestingly, one of the primary targets of cadmium toxicity in the testis is the cytoskeletons of the Sertoli cells, which, in turn, impedes cell junctions in the seminiferous epithelium. In order to expand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…p38, an essential member of the MAPK family, is implicated in exogenous toxin-induced BTB injury. , The p38 signaling pathway is activated in the intestinal epithelial barrier, gastric mucosal barrier, and blood–brain barrier in a DON-induced TJ model of injury. ,, However, whether the damage caused by DON to TJ proteins expression and localization in the BTB is via the p38 signaling pathway is still unclear. In this study, we focused on the action of the p38 signaling pathway and its downstream components in DON-induced injury in testicular TJs.…”
Section: Discussionmentioning
confidence: 99%
“…p38, an essential member of the MAPK family, is implicated in exogenous toxin-induced BTB injury. , The p38 signaling pathway is activated in the intestinal epithelial barrier, gastric mucosal barrier, and blood–brain barrier in a DON-induced TJ model of injury. ,, However, whether the damage caused by DON to TJ proteins expression and localization in the BTB is via the p38 signaling pathway is still unclear. In this study, we focused on the action of the p38 signaling pathway and its downstream components in DON-induced injury in testicular TJs.…”
Section: Discussionmentioning
confidence: 99%
“…Sertoli cells were isolated from the testes of 20-day-old male pups for primary cultures as earlier described [ 25 ] and detailed elsewhere in our laboratory [ 26 ]. Freshly isolated Sertoli cells were seeded on Matrigel (BD Biosciences, San Jose, CA)-coated culture dishes (either 6-, 12-, or 24-well dishes), coverslips (to be placed in 12-well dishes), and bicameral units (Millipore, Burlington, MA; to be placed in 24-well dishes).…”
Section: Methodsmentioning
confidence: 99%
“…Sertoli cells cultured for 3 days were treated with 0.9% NaCl (control) versus CdCl 2 at 1 µM for 6 h for IF or at 3 µM for 24 h for IB, qPCR, and RNA-Seq for transcriptome profiling. The selection of these concentrations and treatment times for specific experiments reported herein was based on the results of a series of pilot experiments, and published in earlier reports [ 25 , 30 32 ], to obtain the notable phenotypes without impeding cell viability. For in vivo experiments, adult rats were treated with CdCl 2 at 3 mg/kg b.w.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…translocation of germ cells (Siu et al, 2009;Wong et al, 2004). Some studies have suggested that the abnormal reproductive function caused by the environmental poison cadmium can be treated by targeting the p38MAPK pathway (Wang et al, 2023;Yu et al, 2008).…”
Section: What Is the Clinical Significancementioning
confidence: 99%